Bell's palsy as an early manifestation of acute lymphoblastic leukemia - Özçakar, L; Akinci, A; Özgöçmen, S; Aksu, S; Çetin, E (Springer-Verlag, 2003)
A 20-year-old man with the complaints of malaise, fever, and tooth gum bleeding presented at a hospital. He was found to have generalized lymphadenopathy, thrombocytopenia, and leukocytosis. Ensuing bone marrow biopsy led to a diagnosis of acute lymphoblastic leukemia (ALL). He also had a sense of facial stretching and difficulty during eating. After clinical examination, he was diagnosed with right-sided peripheral type facial nerve paralysis (Bell's palsy). The magnetic resonance imaging studies demonstrated bilateral facial nerve involvement, predominantly on the right side. The patient received steroid treatment and local facial radiotherapy for Bell's palsy. A concurrent facial exercise program was ordered. Seemingly a less significant diagnosis in a leukemia patient, we considered our case notable since an ALL patient presenting with Bell's palsy, especially at the very beginning of the disease, is not that common. The cases of relapsing ALL reported in the literature initially presenting with the same scenario further strengthen the significance.
Keywords: Bell's palsy; acute lymphoblastic leukemia; magnetic resonance imaging; radiotherapy; physical therapy